2012
DOI: 10.1186/1471-2164-13-540
|View full text |Cite
|
Sign up to set email alerts
|

Response of the goat mammary gland to infection with Staphylococcus aureus revealed by gene expression profiling in milk somatic and white blood cells

Abstract: BackgroundS. aureus is one of the main pathogens responsible for the intra-mammary infection in dairy ruminants. Although much work has been carried out to understand the complex physiological and cellular events that occur in the mammary gland in response to S. aureus, the protective mechanisms are still poorly understood. The objectives of the present study were to investigate gene expression during the early response of the goat mammary gland to an experimental challenge with S. aureus, in order to better u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 48 publications
(51 reference statements)
2
54
0
2
Order By: Relevance
“…Studies conducted so far about cell extraction from milk (2,4,7,14,17) reported that large amounts of milk (50 mL-1000 mL) was required. However, since there are risks related to sterility and degradation in RNA studies, magnitude of milk volumes creates significant problems in transferring the samples from the farm to the laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted so far about cell extraction from milk (2,4,7,14,17) reported that large amounts of milk (50 mL-1000 mL) was required. However, since there are risks related to sterility and degradation in RNA studies, magnitude of milk volumes creates significant problems in transferring the samples from the farm to the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, researchers who had conducted studies both on breast tissue and on somatic cells reported that milk somatic cells can be used as RNA source in the analysis of lipogenic activities of the tissue (14). Generally, most of the studies about RNA extraction from milk somatic cells were conducted on goats (2,4,10), cows (7,14,17,20) and sheep (13) milks. Total milk volume to extract RNA from milk somatic cells changes between 50 mL-1000 mL in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…The same authors also stated that most leukocytes are mobilized from the bloodstream into the mammary tissue after changes in the capillary permeability. Milk from cows with intramammary infections may show increased numbers of immune cells, leading to a predomination of neutrophils, followed by macrophages and lymphocytes, while the number of epithelial cells remains unchanged (12,13). Previous study showed that bovine viral diarrhea affects SCC (8), the lack of information concerning infectious diseases motivated the present study on the relationship between milk composition and quality on dairy cattle with tick fever.…”
Section: Babesia Bovismentioning
confidence: 96%
“…In Argentina, it has been reported that dairy cows experimentally infected by an attenuated strain of A. marginale showed reduction of milk production, as well as fever, sanguíneo hacia el tejido mamario tras cambios en la permeabilidad capilar. La leche de vacas con infecciones intra-mamarias puede presentar un mayor número de células inmunes, lo que lleva a un predominio de neutrófilos, seguido por macrófagos y linfocitos, mientras que el número de células epiteliales permanece sin cambios (12,13). Un estudio anterior mostró que la diarrea viral bovina afecta el valor de SCC (8); la falta de información respecto a las enfermedades infecciosas motivó el presente estudio sobre la relación entre la composición y calidad de la leche en el ganado lechero con fiebre por garrapatas.…”
Section: Babesia Bovisunclassified
“…For example, the IRF1 gene in pigs is overexpressed in endometrial cells during the peri-implantation period, which contributes to establishing successful pregnancy (Joyce et al, 2007). In goats, studies that examined immune response to mammary gland infection with Staphylococcus aureus showed a high increase in IRF1 gene expression compared with other genes that are related to innate resistance to pathogens (Cremonesi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%